Masovne grobnice na području Sarajeva 1992–1995 / Mass Graves in Sarajevo Area 1992-1995 - Arnaut-Haseljić, Meldijana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
During the 1992-1995Aggression against the Republic of Bosnia and Herzegovina various forms of crimes against humanity and international law were been committed, among which the mass killings of civilians are particularly high, followed by the appearance of mass graves as a special form of post crime cover-up. Mass graves, difficulties and problems of their discovery, point to systematic planning, organization, execution of crimes, as well as its concealment, destruction of material evidence and denial. All this was done in order to conceal the crimes, and to prevent their identification, as well as identifying the perpetrators and order givers.